Regulation of MAIT cells through host-derived antigens - Ito, Emi; Yamasaki, Sho (Frontiers in Immunology, 2024)
Mucosal-associated invariant T (MAIT) cells are a major subset of innate-like T cells that function at the interface between innate and acquired immunity. MAIT cells recognize vitamin B2-related metabolites produced by microbes, through semi-invariant T cell receptor (TCR) and contribute to protective immunity. These foreign-derived antigens are presented by a monomorphic antigen presenting molecule, MHC class I-related molecule 1 (MR1). MR1 contains a malleable ligandbinding pocket, allowing for the recognition of compounds with various structures. However, interactions between MR1 and self-derived antigens are not fully understood. Recently, bile acid metabolites were identified as host-derived ligands for MAIT cells. In this review, we will highlight recent findings regarding the recognition of self-antigens by MAIT cells.